الضغوط النفسية والشفقة بالذات كمنبئات بالهناء النفسي لدى أعضاء هيئة التدريس ومعاونيهم المتزوجات بالجامعة - السحيمي، علياء رجب (جامعة بنها - كلية التربية, 2021)
هدف البحث إلى التنبؤ بالهناء النفسي من خلال الشفقة بالذات، والضغوط النفسية لدى أعضاء هيئة التدريس ومعاونيهم من السيدات المتزوجات بالجامعة. وقد تكونت عينة البحث من (180) عضوة من أعضاء هيئة التدريس ومعاونيهم بالجامعات المصرية من السيدات المتزوجات، بواقع (97 مدرس مساعد، و83 مدرس)، واستخدمت الباحثة مقياس الهناء النفسي (2014 ,Ryff)، ومقياس الشفقة بالذات (2003 ,Neff)، ومقياس الضغوط النفسية (إعداد الباحثة)، وباستخدام معاملات الارتباط لبيرسون، واختبار (ت)، وتحليل الانحدار المتعدد، كشفت النتائج أنه توجد علاقات دالة إحصائيا عند مستوى (0.01) بين الهناء النفسي (الأبعاد والدرجة الكلية)، وكل من الضغوط النفسية والشفقة بالذات (الأبعاد والدرجة الكلية)، كذلك لا يوجد فروق دالة إحصائيا بين متوسطات درجات أعضاء هيئة التدريس ومعاونيهم من السيدات المتزوجات في كل من الهناء النفسي، والشفقة بالذات، والضغوط النفسية طبقا لــــ (الدرجة الوظيفية، والتخصص)، ولكن وجدت فروق على بعدي الضغوط الشخصية، والضغوط الاجتماعية والدرجة الكلية طبقا (للتخصص) لصالح الكليات النظرية، كما أن كلا من الضغوط النفسية والشفقة بالذات تسهم في التنبؤ بالهناء النفسي لدى عينة البحث. The research aimed to predict psychological well-being through psychological stress and self-compassion for married female faculty members and their assistances. The research participants were 180 married female faculty members (97 assistant lecturers as well as 83 lecturers) from different Egyptian Universities. The research tools were a psychological well-being scale prepared by (Ryff, 2014), a self-compassion scale by (Neff, 2003), and a psychological stress scale that was prepared by the author of the current research. The results of the research revealed correlative relationship between psychological well-being, psychological stress and self-compassion. There were no differences between faculty members and their assistants in psychological well-being, psychological stress and self-compassion based on (degree, specialization), but there were differences between faculty members and their assistants on the two dimensions of personal and social stress and the total score based on (specialization) in favor of theoretical faculties. Thus, it was indicated that psychological well-being can be predicted through psychological stress and self-compassion.
Keywords: الصحة النفسية -- الضغوط النفسية -- الشفقة بالذات -- هيئة التدريس